Revealing implicit meaning through enthymemes in corporate environmental rhetoric: the case of TM - Islahudin, Hassan Farid; Ahmad, Abdul Mua'ti @ Zamri; Hasan, Hamisah Zaharah; Osman, Mohd Nizam (Faculty of Economics and Management, Universiti Putra Malaysia, 2012)
Companies are now increasingly aware that environmental issues are perceived to be important to all its stakeholders, and previous studies have shown that they have responded by increasing the amount of their environmental disclosures. This research paper argues that corporate annual reports can be viewed as a corpus of persuasive stories, and seeks to examine and describe the argumentative structure of environmental narratives within this document. In conducting this research, rhetorical analysis is performed by analyzing the central storyline as well as the logical enthymemes implicit in the narrative of annual reports published by TM (Telekom Malaysia Berhad) in years 2001 and 2009. The company in question is found to have increased not only the quantity of its disclosures, but also the rhetorical complexity of its environmental arguments. The paper concludes that no analysis of corporate environmental disclosure can be complete without an examination of its implicit meaning by means of a rhetorical analysis in the qualitative tradition of empirical research. From a more pragmatic perspective, practical recommendations are also proposed for corporations seeking to improve the persuasive capacity of their environmental rhetoric.